ANALISIS PELAKSANAAN SISTEM PENJAJARAN MIDDLE DIGIT FILLING TERHADAP EFEKTIVITAS PENYIMPANAN BERKAS REKAM - Ade Irma Suryani; Raisya Nur Azizah (Jurnal Infokes, 2022)
Background: Medical records are confidential medical files belonging to patients, and the storage must be managed properly to maintain the security and confidentiality of medical record files. The medical record storage system requires the right method so that storage is organized. The implementation of the alignment system at Kebonjati Hospital Bandung uses a middle digit filling alignment system, namely storage by aligning medical record files seen from the 2 (two) middle numbers contained in the medical record file map.Objective: This study was conducted to analyze the implementation of the alignment system with the middle digit filling system on the effectiveness of storing medical record files at Kebonjati Hospital, Bandung.Methods: The research was conducted using a qualitative descriptive method. The data collection technique used was literature study, observation and interviews with a population of 4 and 4 people were selected as samples.Results: From the research conducted, it was found that the use of the middle digit filling alignment system in the implementation of centralized medical file storage was considered effective when observed from the number of missing medical record files.Conclusion: Alignment of medical records with the Middle Digit Filling System at Kebonjati Hospital Bandung is effective, because the factor of misfiles is often due to fatigue or lack of thoroughness of the staff.Keywords: Alignment, Storage, Medical Records